2018
DOI: 10.1111/aor.13323
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Exposure Time on von Willebrand Factor Degradation

Abstract: Despite the prevailing use of the continuous flow left ventricular assist devices (cf-LVADs), acquired von Willebrand syndrome (AvWS) associated with cf-LVADs still remains a major complication. As AvWS is known to be dependent on shear stress ( ) and exposure time (t exp ), this study examined the degradation of high molecular weight multimers (HMWM) of von Willebrand factor (vWF) in terms of τ and t exp . Two custom apparatus, i.e., capillary-tubing-type degrader (CTD) and Taylor-Couettetype degrader (TCD) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…For example, turbulent flow conditions are present in severe AS 10,26 and these have been shown to cause excessive cleavage in the presence of ADAMTS13 by our group and others. 12,28 Prior studies conducted by Schneider et al reported VWF extension at SR above 1000 s À1 . 44 At such rates the platelet binding capacity of VWF, mediated by the A1 domain, might be substantial.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, turbulent flow conditions are present in severe AS 10,26 and these have been shown to cause excessive cleavage in the presence of ADAMTS13 by our group and others. 12,28 Prior studies conducted by Schneider et al reported VWF extension at SR above 1000 s À1 . 44 At such rates the platelet binding capacity of VWF, mediated by the A1 domain, might be substantial.…”
Section: Discussionmentioning
confidence: 97%
“…Platelets contain the VWF's binding receptor platelet glycoprotein Ib alpha (GP1ba), and VWF/platelet binding could contribute to cleavage by increasing the force across the VWF molecule. 20,28 Since the goal of our biophysical study was to evaluate the role of elongation and shear rates on VWF cleavage by ADAMTS13, we utilized recombinant VWF (VonvendiÒ) as all molecules in the sample are of similar size. This allowed us to limit the potential variability associated with the heterogeneous size distribution of VWF in plasma that results from the presence of ADAMTS13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choon‐Sik Jhun et al of the Penn State College of Medicine, Hershey, PA, USA investigated the dependence of shear stress (τ) and exposure time (t exp) of acquired von Willebrand syndrome (AvWS) with continuous flow left ventricular assist devices (cf‐LVADs). They investigated these variables on the degradation of high molecular weight multimers (HMWM) of vWF.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…6 With the advent of rotary blood pumps, this figurative "blender" phenomenon appeared as a common denominator for all such devices and became accepted as a necessary shortcoming of this technology. Curiously, while it was clear that high shear stress in the continuous flow LVADs reduces the levels of HMvWF, 7 it was less obvious how or if different pump designs may influence the integrity of these multimers.…”
Section: Implantation Of Left Ventricular Assist Devices (Lvads)mentioning
confidence: 99%